Distribuição das peritonites por regiões climáticas brasileiras em uma coorte de pacientes em diálise peritoneal - Melere, Camila Borges Mosmann (2019)
Introduction: the prevalence of chronic kidney disease (CKD) in the world population is high. In Brazil, approximately 122 thousand patients undergo dialysis treatment, of which 7.9% are on peritoneal dialysis (PD). Peritonitis is the main cause of morbimortality and method failure in this therapeutic modality. In addition to the following main risk factors: black race, diabetes mellitus (DM), advanced age, obesity, malnutrition, chronic inflammation, decreased residual renal function, and previous peritonitis; social factors, such as low schooling level, distance from home to dialysis center, and geographic region have also been described. The geographical location may determine differences in the clinical characteristics and outcomes of dialysis patients, although within the same territory, especially in a country with such a climate diversity like Brazil. The changes in temperature and in humidity may play a role in developing this infection. Objective: This study aims to outline the distribution of peritonitis in a cohort of patients on peritoneal dialysis according to the climate regions in Brazil. Method: retrospective multicenter cohort study; data of 1,631 patients who were incident on peritoneal dialysis (PD), presented at least one episode of peritonitis, and had completed at least 90-day therapy were collected from the BRAZPD study (Multicenter Study of Peritoneal Dialysis in Brazil) and analyzed. Information on temperature and humidity were evaluated in each Brazilian region during infection period. Such information referred to the average values in the month which patients developed peritonitis and it was collected from the National Meteorology Institute (INMET) database. The analysis was carried out through the division of the country according to its climate regions, following the Geography and Statistics Brazilian Institute (IBGE) guidelines. Results: a total of 9,905 adult patients from 122 Brazilian centers were included; 2,562 presented episodes of infection. Mean age of 59.2 ± 16,2 yrs. and 53.3% (n=870) of women. It was detected an increase in the number of cases in January, predominance of negative culture and, among episodes with positive culture, gram-positive (GP) predominanted. The present study showed an overall rate of 0.30 episodes per patient/year and peritonitis rate comparison demonstrates a statistically significant difference between regions (p<0.001). Association between humidity and peritonitis in the Central Tropical region (r=0.58) and potential association were found between the number of infections and the average temperature in this region (r=0.47), highest temperature in the Equatorial region (r=0.44), and a potential negative association between the number of infections and humidity in the Equatorial region (r=0.48). Conclusion: it was possible to observe that the occurrence of peritonitis varies among Brazilian climate regions, with a higher occurrence in the month of January. We found an association between humidity and peritonitis in the Central Tropical region and a potential association between the number of infections and the average temperature in this region, highest temperature in the Equatorial region, and a potential negative association between the number of infections and humidity in the Equatorial region. Gram-positive bacteria caused most of the episodes and maintained a consistent distribution throughout the year.